Study on the effect of magnesium on leaf metabolites, growth and quality of tea tree - Zhang, Ying; Zhang, Qi; Wang, Yuhua; Lin, Shaoxiong; Chen, Meihui; Cheng, Pengyuan; Du, Mengru; Jia, Xiaoli; Ye, Jianghua; Wang, Haibin (Frontiers in Plant Science, 2023)
Magnesium (Mg) is one of the essential elements for the growth of tea trees. In this study, we investigated changes in metabolites, photosynthetic fluorescence parameters and quality indexes of tea leaves under different concentrations of magnesium treatment, and the results showed that there were no significant differences in the quantity and total content of metabolites in tea leaves under different Mg concentrations. The results of volcano map analysis showed that the content of 235 metabolites in tea leaves showed an increasing trend and the content of 243 metabolites showed a decreasing trend with the increase of Mg concentration. The results of the combined analysis of the OPLS-DA model and bubble map showed that 45 characteristic metabolites were screened at different concentrations of Mg. Among these, the content of 24 characteristic metabolites showed an increasing trend and 21 characteristic metabolites showed a decreasing trend with the increase of Mg concentrations. The results of KEEG pathway enrichment showed that 24 characteristic metabolites with a upward trend were significantly enriched in saccharides metabolism, nucleic acid metabolism and vitamin metabolism, while the 21 characteristic metabolites with a downward trend were enriched in the synthesis of plant secondary metabolites, phenylpropanoid biosynthesis, biosynthesis of terpenoids, synthesis and metabolism of alkaloids, and synthesis and metabolism of amino acids. It can be inferred that Mg regulation was beneficial to enhance the photosynthetic capacity of tea trees, improve the accumulation and metabolism of carbohydrate substances in tea trees, and thus promoted the growth of tea trees, but was not conducive to the synthesis of secondary metabolites and amino acids related to tea quality. The results of photosynthetic fluorescence parameters and quality indexes of the tea tree confirmed the conclusion predicted by metabolomics. This study provided a reference for regulating of the growth and quality of tea trees with Mg fertilizer in tea plantations.